Serial and parallel processing in reading: Investigating the effects of parafoveal orthographic information on nonisolated word recognition. - Dare, Natasha; Shillcock, Richard (Quarterly Journal of Experimental Psychology, 2013)
We present a novel lexical decision task and three boundary paradigm eye-tracking experiments that clarify the picture of parallel processing in word recognition in context. First, we show that lexical decision is facilitated by associated letter information to the left and right of the word, with no apparent hemispheric specificity. Second, we show that parafoveal preview of a repeat of wordnat wordn +1 facilitates reading of wordnrelative to a control condition with an unrelated word at wordn +1. Third, using a version of the boundary paradigm that allowed for a regressive eye movement, we show no parafoveal “postview” effect on reading wordnof repeating wordnat wordn –1.Fourth, we repeat the second experiment but compare the effects of parafoveal previews consisting of a repeated wordnwith a transposed central bigram (e.g.,caotforcoat) and a substituted central bigram (e.g.,ceitforcoat), showing the latter to have a deleterious effect on processing wordn, thereby demonstrating that the parafoveal preview effect is at least orthographic and not purely visual.